Semiconductor film and composite substrate

A semiconductor film with a solid solution phase of ε-Ga2O3, featuring a narrow Raman peak half-width, addresses impurity-related issues, enhancing crystallinity and reducing variations, thereby improving the performance of ε-Ga2O3-based high electron mobility transistors.

JP7620719B2Active Publication Date: 2025-01-23NGK CORP
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2023543703
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-08-27
Filing Date
2022-06-09
Publication Date
2025-01-23
Estimated Expiration
2042-06-09

AI Technical Summary

Technical Problem

Existing semiconductor films based on ε-Ga2O3 face challenges due to high impurity concentrations, which affect their crystallinity and properties, making it difficult to achieve consistent performance in high electron mobility transistors (HEMTs).

Method used

A semiconductor film with a main phase composed of a solid solution of ε-Ga2O3, characterized by a half-width of nearby peaks in the Raman spectrum of 10cm-1 or less, ensuring high crystallinity and low impurity concentrations, particularly in transition metals, alkali metals, and halogen elements, is developed.

Benefits of technology

The solution results in a semiconductor film with enhanced crystallinity and reduced impurity concentrations, improving the consistency and performance of ε-Ga2O3-based high electron mobility transistors (HEMTs) by minimizing variations in film properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620719000003
    Figure 0007620719000003
  • Figure 0007620719000004
    Figure 0007620719000004
  • Figure 0007620719000005
    Figure 0007620719000005
Patent Text Reader

Abstract

Provided is an ε-Ga2O3-based semiconductor film having a low impurity concentration. The semiconductor film contains crystals each composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution as a main phase, in which the half width of a peak appearing at around 250 cm-1 in a Raman spectrum of the semiconductor film as measured by laser Raman spectroscopy is 10 cm-1 or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to an ε-Ga2O3-based semiconductor film and a composite substrate including the same. [Background technology]

[0002] Gallium oxide (Ga2O3) has recently attracted attention as a semiconductor material. Gallium oxide is known to have five crystalline forms: α, β, γ, δ, and ε. Among these, ε-Ga2O3 has a bandgap of approximately 5 eV, is highly stable up to approximately 870°C, and allows for bandgap control through alloy formation. Furthermore, while the generation of two-dimensional electron gas is required for application in high-electron-mobility transistors (HEMTs), ε-Ga2O3 possesses a crystalline structure exhibiting spontaneous polarization, making it a promising candidate for next-generation power semiconductor materials with high breakdown voltage and low power consumption. Because ε-Ga2O3 is metastable, single-crystal substrates have not yet been developed; instead, it is grown by heteroepitaxial growth on heterogeneous substrates.

[0003] For example, Patent Document 1 (Japanese Patent No. 6436538) discloses an ε-Ga2O3 single crystal with a low impurity concentration that is applicable to semiconductor devices and that is fabricated using the HVPE (halide vapor phase epitaxy) method. Non-Patent Document 1 (Yuichi Oshima et al. "Epitaxial growth of phase-pure ε-Ga2O3 by halide vapor phase epitaxy" J. Appl. Phys, 118, 085301 (2015)) discloses an ε-Ga2O3 semiconductor film formed on a GaN substrate or an AlN substrate by the HVPE method. Patent Document 2 (JP 2019-46984 A) discloses a method for manufacturing a semiconductor device with excellent semiconductor properties by forming, by a mist CVD method, a first semiconductor film containing, as its main component, semiconductor crystals having a metastable crystal structure, and a second semiconductor film (mainly ε-Ga2O3) that has a different composition from the main component of the first semiconductor film and contains, as its main component, semiconductor crystals having a hexagonal crystal structure.

[0004] ε-Ga2O3 has ferroelectric properties and a crystal structure that generates spontaneous polarization, making it promising for HEMT applications, similar to GaN. The electrical conductivity and other properties of such semiconductors are generally controlled by doping. For example, methods such as incorporating dopants into the film-forming raw materials or ion implantation are used. However, unlike intentional doping, impurities from the film-forming chamber or the raw materials can be present in the film. These impurities can cause variations in the properties of semiconductor films, so it is desirable to minimize them as much as possible. In particular, the inclusion of transition metal elements such as Fe and Ti, alkali metals such as Na, and halogen elements such as F in semiconductor films can easily cause variations in the properties of semiconductor films.

[0005] Incidentally, Raman spectroscopy is known as a method for evaluating the crystallinity of semiconductor films. In Raman spectroscopy, a substance is irradiated with light to cause scattering, and the scattered light is then separated to obtain a Raman spectrum, thereby evaluating the crystallinity of the substance. For example, if the half-width of a specific Raman peak in the Raman spectrum of a certain substance is small, the crystallinity of the substance can be evaluated as high. For example, Non-Patent Document 2 (Francesco Boschi, "Growth and Investigation of Different Gallium Oxide Polymorphs," UNIVERSITA DEGLI STUDI DI PARMA, Dottorato di Ricerca in Fisica, Ciclo XXIX, 2017) reports the Raman spectrum of an ε-Ga2O3 film formed on a c-plane sapphire substrate, but the 250 cm -1 The half-width of the peak in the vicinity was relatively broad, indicating that the film had low crystallinity. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 6436538 [Patent Document 2] Japanese Patent Application Laid-Open No. 2019-46984

Non-Patent Document

[0007]

Non-Patent Document 1

Non-Patent Document 2

Non-Patent Document 3

Non-Patent Document 4

Summary of the Invention

[0008] As mentioned above, ε-Ga2O3 has ferroelectric properties, a crystal structure that generates spontaneous polarization, and the advantage of bandgap control through alloy formation. Therefore, like GaN, it is expected to be applied to high electron mobility transistors (HEMTs). However, impurities can be contained in the film, which can cause variations in the properties of the semiconductor film. Thus, it has been difficult to obtain ε-Ga2O3-based semiconductor films with few impurities.

[0009] The present inventors have now discovered that the 250 cm -1 It was found that the impurity concentration of the ε-Ga2O3-based semiconductor film can be reduced by controlling the half-width of the peak in the vicinity to increase the crystallinity of the ε-Ga2O3-based semiconductor film.

[0010] Therefore, an object of the present invention is to provide an ε-Ga2O3-based semiconductor film having a low impurity concentration.

[0011] According to the present invention, the following aspects are provided. [Aspect 1] A semiconductor film having a crystal phase composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution, 250 cm in the Raman spectrum of the semiconductor film measured by laser Raman spectroscopy -1 The half-width of the peak in the vicinity is 10 cm -1 The semiconductor film is as follows: [Aspect 2] The surface of the semiconductor film is measured by laser Raman spectroscopy at the center point X of the largest circle inscribed in the outer periphery of the semiconductor film and at each of the four outer periphery points A, B, C, and D, and the Raman spectrum of the semiconductor film is -1 The half-width of the peak in the vicinity is 10 cm -1 is as follows: 2. The semiconductor film of claim 1, wherein the perimeter points A, B, C, and D are determined such that: i) a line connecting the perimeter points A and C and a line connecting the perimeter points B and D intersect at right angles at the center point X; and ii) the shortest distance from the outer edge of the semiconductor film to each of the perimeter points A, B, C, and D is 1 / 5 of the radius of the semiconductor film. [Aspect 3] In the Raman spectrum of the semiconductor film, -1 Peak intensity I near 250 260cm -1 Peak intensity I near 260 Peak intensity ratio I to 250 / I 260 is 2.0 or more. [Aspect 4] 113 cm in the Raman spectrum of the semiconductor film -1 The half-width of the peak in the vicinity is 10 cm -1 A semiconductor film according to any one of aspects 1 to 3, wherein: [Aspect 5] The Ti concentration at the surface of the semiconductor film is 1.0×10 15 atoms / cm 3 5. The semiconductor film according to any one of aspects 1 to 4, wherein: [Aspect 6] The Fe concentration at the surface of the semiconductor film is 1.0×10 15 atoms / cm 3 6. The semiconductor film according to any one of aspects 1 to 5, wherein: [Aspect 7] The Na concentration at the surface of the semiconductor film is 2.0×10 13 atoms / cm 3 7. The semiconductor film according to any one of aspects 1 to 6, wherein: [Aspect 8] The F concentration at the surface of the semiconductor film is 2.0×10 15 atoms / cm 3 A semiconductor film according to any one of aspects 1 to 7, wherein: [Aspect 9] The Si concentration at the surface of the semiconductor film is 1.0×10 16 atoms / cm3 A semiconductor film according to any one of aspects 1 to 8, wherein: [Aspect 10] A composite substrate comprising a GaN single crystal substrate and the semiconductor film according to any one of aspects 1 to 9 formed on the GaN single crystal substrate. [Brief explanation of the drawings]

[0012] [Figure 1] FIG. 2 is a diagram for explaining the positions of a center point X and four outer periphery points A, B, C, and D on the surface of a semiconductor film of the present invention. [Figure 2] FIG. 1 is a schematic cross-sectional view showing the configuration of an HVPE (halide vapor phase epitaxy) apparatus. [Figure 3] FIG. 1 is a schematic cross-sectional view showing the configuration of a mist CVD (chemical vapor deposition) apparatus. [Figure 4] 1 shows a Raman spectrum measured in the semiconductor film prepared in Example 1. DETAILED DESCRIPTION OF THE INVENTION

[0013] Semiconductor film The semiconductor film according to the present invention has a crystal composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution as a main phase. Therefore, the semiconductor film according to the present invention can be called an ε-Ga2O3-based semiconductor film. Furthermore, this semiconductor film has a peak at 250 cm in the Raman spectrum of the semiconductor film measured by laser Raman spectroscopy. -1 The half-width of the peak in the vicinity is 10 cm -1 Thus, the 250 cm -1 By controlling the half-width of the peak in the vicinity of the peak and increasing the crystallinity of the ε-Ga2O3-based semiconductor film, the impurity concentration of the ε-Ga2O3-based semiconductor film can be reduced. Here, "in the vicinity" of the wavenumber (Raman shift) in the Raman spectrum typically refers to a wavenumber within ±5.0 cm from the wavenumber. -1 For example, "250cm" means a range -1 The peak around 245-255 cm -1 It means "peak of".

[0014] As mentioned above, ε-Ga2O3 has the advantages of ferroelectric properties, a crystal structure that generates spontaneous polarization, and bandgap control through alloy formation. Therefore, like GaN, it is expected to be applied to high electron mobility transistors (HEMTs). However, impurities can be contained in the film, which can cause variations in the properties of the semiconductor film. Thus, it has been difficult to obtain ε-Ga2O3-based semiconductor films with low impurities. In this regard, the semiconductor film of the present invention can reduce the impurity concentration of the ε-Ga2O3-based semiconductor film by improving the film's crystallinity, thereby advantageously resolving the above-mentioned problems.

[0015] This semiconductor film has a surface area measured by laser Raman spectroscopy at the center point X of the largest circle inscribed in the outer periphery of the semiconductor film (hereinafter referred to as the largest inscribed circle) and at each of the four outer periphery points A, B, C, and D, where the area is within a range of 250 cm in the Raman spectrum of the semiconductor film. -1 The half-width of the peak in the vicinity is 10 cm -1 Preferably, the outer periphery points A, B, C, and D are determined so that i) a line connecting outer periphery points A and C and a line connecting outer periphery points B and D intersect at a right angle at the center point X, and ii) the shortest distance from the outer edge of the semiconductor film to each of outer periphery points A, B, C, and D is 1 / 5 of the radius of the semiconductor film. Also, this semiconductor film is preferably circular, and in this case, the maximum inscribed circle of semiconductor film 10 can coincide with the outer edge as shown in FIG. 1. In this way, at five points sufficiently spaced from each other, the 250 cm -1 The half-width of the peak in the vicinity is 10 cm -1 The following ε-Ga2O3-based semiconductor film can be said to have a small half-width over a wide range from the center to the periphery of the film, and such a semiconductor film has high crystallinity and a low impurity concentration.

[0016] The semiconductor film of the present invention has a Raman spectrum of 250 cm -1 The half-width of the peak in the vicinity is 10 cm -1less than 8.0 cm, preferably -1 More preferably, it is 7.0 cm or less. -1 From the viewpoint of reducing the impurity concentration, the 250 cm -1 The smaller the half-width of the peak in the vicinity, the better. -1 The lower limit of the half-width of the peak in the vicinity is not particularly limited, but is typically 0.1 cm -1 More than 1.0 cm, more typically -1 That's all.

[0017] The semiconductor film of the present invention has a Raman spectrum (preferably at the center point X of the largest inscribed circle and at each of the outer periphery points A, B, C, and D) of 250 cm -1 Peak intensity I near 250 260cm -1 Peak intensity I near 260 Peak intensity ratio I to 250 / I 260 is preferably 2.0 or more, more preferably 5.0 or more, and even more preferably 8.0 or more. 250 / I 260 The upper limit is not particularly limited because a higher value is better, but it is typically 50 or less. -1 "Around" typically refers to 250 cm -1 The wave number of the peak in the vicinity of 10 cm -1 For example, 250 cm -1 The top of the nearby peak is 245cm -1 If it was, "260cm -1 The peak near the -1 This means the peak of

[0018] The semiconductor film of the present invention has a Raman spectrum of 113 cm (preferably at the center point X and the outer periphery points A, B, C, and D of the largest inscribed circle). -1 The half-width of the peak in the vicinity is 10 cm -1 Preferably it is equal to or less than 8.0 cm, more preferably 8.0 cm -1 and more preferably 6.0 cm or less.-1 From the viewpoint of reducing the impurity concentration, the 113 cm -1 The smaller the half-width of the peak in the vicinity, the better. -1 The lower limit of the half-width of the peak in the vicinity is not particularly limited, but is typically 0.1 cm -1 More than 1.0 cm, more typically -1 That's all.

[0019] As mentioned above, when a semiconductor film contains transition metal elements such as Fe and Ti, alkali metals such as Na, or halogen elements such as F, the semiconductor film is likely to have variations in its properties. In this regard, the semiconductor film of the present invention has high crystallinity, so it is possible to reduce the amount of impurities that can be contained. That is, the Ti concentration on the surface of the semiconductor film is 1.0×10 15 atoms / cm 3 It is preferably equal to or less than 1.0×10 14 atoms / cm 3 or less, more preferably 1.0 × 10 13 atoms / cm 3 The Fe concentration at the surface of the semiconductor film is 1.0 × 10 15 atoms / cm 3 It is preferably equal to or less than 1.0×10 14 atoms / cm 3 or less, more preferably 1.0 × 10 13 atoms / cm 3 The Na concentration at the surface of the semiconductor film is 2.0 × 10 13 atoms / cm 3 It is preferably equal to or less than 1.0×10 12 atoms / cm 3 or less, more preferably 1.0 × 10 11 atoms / cm 3 The F concentration at the surface of the semiconductor film is 2.0 × 10 15 atoms / cm 3 It is preferably equal to or less than 1.0×10 14 atoms / cm 3 or less, more preferably 1.0 × 1013 atoms / cm 3 Similarly, the Si concentration at the surface of the semiconductor film is 1.0 × 10 16 atoms / cm 3 It is preferably equal to or less than 1.0×10 15 atoms / cm 3 or less, more preferably 1.0 × 10 14 atoms / cm 3 The lower the concentration of each of the elements Ti, Fe, Na, F, and Si on the surface of the semiconductor film, the better, so there is no particular lower limit.

[0020] However, Si may be used as a dopant for the semiconductor film, and in that case, the Si concentration at the surface of the semiconductor film may exceed the upper limit of the above-mentioned preferred range, for example, 1.0×10 15 ~1.0×10 21 atoms / cm 3 It is possible.

[0021] As described above, the semiconductor film of the present invention has a crystal composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution as its main phase. As used herein, "having a crystal composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution as its main phase" means that the crystal composed of ε-Ga2O3 or an ε-Ga2O3-based solid solution accounts for 80% by weight or more of the semiconductor film, preferably 90% by weight or more, more preferably 95% by weight or more, even more preferably 97% by weight or more, particularly preferably 99% by weight or more, and most preferably 100% by weight. An ε-Ga2O3-based solid solution is a solid solution of ε-Ga2O3 with other components. For example, the semiconductor film of the present invention may be composed of an ε-Ga2O3-based solid solution in which one or more components selected from the group consisting of Cr2O3, Fe2O3, Ti2O3, V2O3, Ir2O3, Rh2O3, In2O3, and Al2O3 are solid-solved in ε-Ga2O3. Furthermore, by dissolving these components in solid solution, it becomes possible to control the band gap, electrical properties, and / or lattice constant of the semiconductor film. The amount of these components dissolved in solid solution can be appropriately changed according to the desired properties. Furthermore, the ε-Ga2O3-based solid solution may contain other components such as Si, Sn, Ge, N, and Mg as dopants.

[0022] However, the crystal structure of ε-Ga2O3 has not yet been fully elucidated at the current technical level. Therefore, it is possible that a material identified as κ-Ga2O3 in crystal structure analysis may also be identified as ε-Ga2O3, or vice versa. For example, Non-Patent Document 3 (Ildiko Cora et al., "The Real Structure of ε-Ga2O3 and Its Relation to κ-Phase," CrystEngComm, 2017, 19, 1509-1516) suggests that the crystal structure of ε-Ga2O3 (hexagonal) may be confused with the crystal structure of κ-Ga2O3 (orthorhombic) depending on the resolution of the probe technology. Therefore, in this specification, the term "ε-Ga2O3" refers not only to ε-Ga2O3 but also to κ-Ga2O3. That is, in this specification, even if a material is identified as having the crystal structure of κ-Ga2O3, it is considered to be "ε-Ga2O3" and is included in the term "ε-Ga2O3".

[0023] The orientation of the ε-Ga2O3-based semiconductor film of the present invention in the approximately normal direction is not particularly limited, but c-axis orientation is preferred. However, typical ε-Ga2O3-based semiconductor films are composed of ε-Ga2O3 or a mixed crystal of ε-Ga2O3 and a different material, and are oriented along two axes, the c-axis and the a-axis. As long as they are biaxially oriented, the ε-Ga2O3-based semiconductor film may be a mosaic crystal. A mosaic crystal is a collection of crystals that do not have clear grain boundaries but whose orientation orientations, along either the c-axis or the a-axis, are slightly different. The method for evaluating biaxial orientation is not particularly limited, but known analytical techniques such as EBSD (Electron Backscatter Diffraction Patterns) and X-ray pole figures can be used. For example, when using EBSD, inverse pole figure mapping of the surface (film surface) of the biaxially oriented ε-Ga2O3 film or a cross section perpendicular to the film surface is measured. In the obtained inverse pole figure mapping, when two conditions are satisfied: (A) the film surface is oriented in a specific direction, and (B) the film surface is oriented in a direction approximately perpendicular to the normal direction, along an axis perpendicular to the orientation direction of the approximately normal direction. In other words, when the above two conditions are satisfied, it is determined that the film is oriented in two axes, the c-axis and the a-axis. For example, when the approximately normal direction to the film surface is oriented along the c-axis, the approximately in-plane direction should be oriented in a specific direction (e.g., the a-axis) perpendicular to the c-axis.

[0024] The semiconductor film of the present invention may have a size such that the diameter of the largest circle inscribed in its outer periphery (i.e., the largest inscribed circle) is 5.08 cm (2 inches) or more, and the diameter of the largest inscribed circle may be 10.0 cm or more. The upper limit of the diameter of the largest inscribed circle is not particularly limited, but is typically 30.0 cm or less, more typically 20.0 cm or less. A typical semiconductor film is circular, and in this case, the diameter of the largest inscribed circle of semiconductor film 10 may be the same as the diameter of semiconductor film 10, as shown in FIG. 1 . Note that, in this specification, the "circular shape" does not necessarily mean a perfect circle, but may also mean a roughly circular shape that can be recognized as a circle overall. For example, the circle may have a shape in which a portion is notched for identifying the crystal orientation or for other purposes, or a shape in which a slit is provided in a portion of the circle. In such cases, the size may be determined based on the diameter of the largest circle inscribed in the outer periphery excluding the notched outer periphery or the slit. The semiconductor film of the present invention exhibits a 250 cm Raman spectrum. -1 The half-width of the peak in the vicinity is 10 cm -1 The center point X and the periphery points A, B, C, and D are merely defined as an example for convenience's sake so that a representative peak half width of the entire semiconductor film can be evaluated. Therefore, in order to uniquely determine the positions of the center point X and the periphery points A, B, C, and D, the shape of the semiconductor film is preferably described as circular, but the essential meaning does not change even if the shape of the semiconductor film is not circular. For example, even if the shape of the semiconductor film is square or rectangular (oblong), the 250 cm -1 In the semiconductor film of this invention, if the half width of the peak in the vicinity is small, it is included in the semiconductor film of this invention. In the semiconductor film of this shape, when a square or rectangular semiconductor film is viewed from above, the largest circle (maximum inscribed circle) inscribed in the outer periphery of the film is defined as a virtual circle, and the positions of the outer periphery points A, B, C, and D can be determined from the center point X of the virtual circle and the diameter of the virtual circle (similar to the case of the circular semiconductor film described above). The center point X and the outer periphery points A, B, C, and D determined in this way can be determined as 250 cm -1By evaluating the half-width of the peak near the slit, it is possible to perform the same evaluation as for a circular semiconductor film. Note that even if a slit is provided in part of a square or rectangular semiconductor film, the maximum circle inscribed in the outer periphery of the film when the square or rectangular semiconductor film is viewed from above (maximum inscribed circle) is still defined as the virtual circle.

[0025] The semiconductor film of the present invention may contain a Group 14 element as a dopant. Here, the Group 14 element refers to the Group 14 element according to the periodic table established by IUPAC (International Union of Pure and Applied Chemistry), specifically any one of carbon (C), silicon (Si), germanium (Ge), tin (Sn), and lead (Pb). The total content of C, Ge, Sn, and Pb as dopants (Group 14 elements) in the semiconductor film is preferably 1.0×10 15 ~1.0×10 21 / cm 3 , more preferably 1.0 × 10 17 ~1.0×10 19 / cm 3 It is preferable that these dopants are distributed homogeneously in the film, and that the dopant concentrations on the front and back surfaces of the semiconductor film are approximately the same.

[0026] The thickness of the semiconductor film of the present invention may be adjusted appropriately from the viewpoint of cost and required properties. That is, if the film is too thick, it takes a long time to form, so from the viewpoint of cost, it is preferable not to make the film too thick. On the other hand, in order to improve the crystal quality, it is preferable to make the film thick to a certain extent. In this way, the film thickness may be adjusted appropriately to match the desired properties.

[0027] The semiconductor film of the present invention may be in the form of a freestanding film. Alternatively, a semiconductor film formed on a base substrate for film formation may be separated and transferred to another support substrate. The material of the other support substrate is not particularly limited, and a suitable one may be selected from the viewpoint of material properties. For example, from the viewpoint of thermal conductivity, metal substrates such as Cu, and ceramic substrates such as SiC and AlN are preferred. It is also preferable to use a substrate with a thermal expansion coefficient of 6 to 13 ppm / K at 25 to 400°C. Using a support substrate with such a thermal expansion coefficient can reduce the difference in thermal expansion with the semiconductor film, thereby suppressing cracking and film peeling in the semiconductor film due to thermal stress. An example of such a support substrate is a substrate composed of a Cu-Mo composite metal. The composite ratio of Cu and Mo can be appropriately selected taking into consideration factors such as thermal expansion coefficient matching with the semiconductor film, thermal conductivity, and electrical conductivity.

[0028] Semiconductor film manufacturing method The semiconductor film of the present invention can be preferably produced by using a GaN single crystal substrate as a base substrate and depositing an ε-Ga2O3-based material thereon. While known methods can be used to form the semiconductor layer, preferred examples include mist CVD (mist chemical vapor deposition), HVPE (halide vapor phase epitaxy), MBE (molecular beam epitaxy), MOCVD (metal organic chemical vapor deposition), and hydrothermal synthesis. Mist CVD or HVPE is particularly preferred. In vapor phase epitaxy methods such as mist CVD or HVPE, the thickness of the base substrate is preferably thicker to suppress warping, preferably 0.5 mm or more, more preferably 0.8 mm or more, and even more preferably 1.4 mm or more. On the other hand, a thinner thickness is preferable from a cost perspective, preferably 1.0 mm or less, more preferably 0.5 mm or less. In this way, the thickness of the base substrate can be appropriately adjusted to match the desired characteristics. The upper limit of the thickness of the base substrate is not particularly limited, but is typically 5.0 mm or less, more typically 4.0 mm or less. -1 The half-width of the peak in the vicinity is 10 cm -1A small ε-Ga2O3-based semiconductor film having a thickness of 1000 nm or less can be preferably realized by depositing the film while rotating the base substrate.

[0029] The HVPE method and the mist CVD method, which are particularly preferred film formation methods, will be described below.

[0030] HVPE (halide vapor phase epitaxy) is a type of CVD method that can be used to deposit compound semiconductors such as Ga2O3 and GaN. In this method, gallium halide gas is generated by reacting a Ga source with a halide, and is then supplied to the substrate for deposition. O2 gas is simultaneously supplied to the substrate, and the gallium halide gas reacts with the O2 gas to grow Ga2O3 on the substrate. This method allows for high-speed and thick film growth and has a wide industrial track record, with examples of deposition of not only ε-Ga2O3 but also α-Ga2O3 and β-Ga2O3.

[0031] 2 shows an example of a vapor phase growth apparatus (HVPE apparatus) using the HVPE method. The HVPE apparatus 20 includes a reactor 22, a susceptor 26 on which a substrate 24 for deposition is placed, an oxygen source supply source 30, a carrier gas supply source 28, a GeCl4 supply source 32, a Ga source supply source 34, a heater 36, and a gas exhaust unit 38. The reactor 22 may be any reactor that does not react with the source material, such as a quartz tube. The heater 36 may be any heater that can heat up to at least 700°C (preferably 900°C or higher), such as a resistance heater.

[0032] The Ga source 34 contains metallic Ga and is supplied with a halogen gas or hydrogen halide gas, such as HCl. The halogen gas or halide gas is preferably Cl2 or HCl. The supplied halogen gas or halide gas reacts with the metallic Ga to produce gallium halide gas, which is then supplied to the base substrate 24. The gallium halide gas preferably contains GaCl and / or GaCl3. The oxygen source 30 can supply an oxygen source selected from the group consisting of O2, H2O, and N2O, with O2 being preferred. These oxygen source gases are supplied to the base substrate simultaneously with the gallium halide gas. The GeCl4 source 32 supplies GeCl4 vapor generated by bubbling GeCl4 liquid into the reactor 22. The Ga source and oxygen source gas may be supplied together with a carrier gas such as N2 or a rare gas.

[0033] The gas exhaust unit 38 may be connected to a vacuum pump such as a diffusion pump or a rotary pump, and may not only exhaust unreacted gases from the reactor 22 but also control the inside of the reactor 22 to a reduced pressure, thereby suppressing gas phase reactions and improving the growth rate distribution.

[0034] The heater 36 is used to heat the base substrate 24 to a predetermined temperature, and gallium halide gas and oxygen source gas are simultaneously supplied to form ε-Ga2O3 on the base substrate 24. The film formation temperature is not particularly limited as long as ε-Ga2O3 is formed and impurities in the film are reduced, but is typically 250°C to 900°C. The partial pressures of the Ga source gas and oxygen source gas are also not particularly limited. For example, the partial pressure of the Ga source gas (gallium halide gas) may be in the range of 0.05 kPa to 10 kPa, and the partial pressure of the oxygen source gas may be in the range of 0.25 kPa to 50 kPa.

[0035] When forming an ε-Ga2O3-based semiconductor film containing a Group 14 element as a dopant, or when forming a mixed crystal film containing an ε-Ga2O3 element containing oxides of In or Al, a separate supply source (e.g., GeCl4 supply source 32 in FIG. 2) may be provided to supply the halide or the like, or a mixture of halides may be supplied from a Ga source supply source 34. Alternatively, a material containing a Group 14 element, In, Al, or the like may be placed in the same location as the metallic Ga, reacted with a halogen gas or hydrogen halide gas, and supplied as a halogen. The halogen gas supplied to the base substrate 24 reacts with the oxygen source gas to form an oxide, similar to the gallium halide, and is then incorporated into the ε-Ga2O3-based semiconductor film.

[0036] The mist CVD method involves atomizing or condensing a raw material solution to generate mist or droplets, transporting the mist or droplets using a carrier gas to a film-forming chamber equipped with a substrate, and thermally decomposing and chemically reacting the mist or droplets in the film-forming chamber to form and grow a film on the substrate. This technique does not require a vacuum process and can produce a large number of samples in a short time. Figure 3 shows an example of a mist CVD apparatus. The mist CVD apparatus 40 shown in Figure 3 includes a mist-generating chamber 42 that generates mist M from a carrier gas G and raw material solution L, and a film-forming chamber 50 that sprays the mist M onto a substrate 56 to form a semiconductor film 58 through thermal decomposition and chemical reaction. The mist-generating chamber 42 includes a carrier gas inlet 44 through which carrier gas G is introduced, an ultrasonic vibrator 46 installed within the mist-generating chamber 42, and a duct 48 that transports the mist M generated in the mist-generating chamber 42 to the film-forming chamber 50. The raw material solution L is contained within the mist-generating chamber 42. The ultrasonic vibrator 46 is configured to apply ultrasonic vibrations to the raw material solution L to generate mist M together with carrier gas G. The film formation chamber 50 includes a nozzle 52 for spraying the mist M introduced through the duct 48 onto a substrate 56, a stage 54 to which the substrate 56 is fixed, a heater 62 provided near the back surface of the stage 54 for heating the stage 54 and the substrate 56, and an exhaust port 64 for discharging the carrier gas G.

[0037] The raw material solution L used in the mist CVD method is not limited as long as it can produce an ε-Ga2O3-based semiconductor film. Examples include organometallic complexes or halides of Ga and / or metals that form solid solutions with Ga dissolved in a solvent. Examples of organometallic complexes include acetylacetonate complexes. When a dopant is added to the semiconductor layer, a solution of the dopant component may be added to the raw material solution. Furthermore, an additive such as hydrochloric acid may be added to the raw material solution. Water, alcohol, or the like may be used as the solvent.

[0038] Next, the obtained raw material solution L is atomized or converted into droplets to generate mist M or droplets. A preferred example of a method for atomizing or converting into droplets is a technique in which the raw material solution L is vibrated using an ultrasonic vibrator 46. Thereafter, the obtained mist M or droplets are transported to the film formation chamber 50 using a carrier gas G. The carrier gas G is not particularly limited, but one or more of an inert gas such as oxygen, ozone, or nitrogen, and a reducing gas such as hydrogen can be used.

[0039] The film formation chamber 50 is equipped with a substrate 56. The mist M or droplets transported to the film formation chamber 50 are thermally decomposed and chemically reacted therein to form a semiconductor film 58 on the substrate 56. The reaction temperature varies depending on the type of raw material solution L, but is preferably 300 to 800°C, and more preferably 400 to 700°C. The atmosphere within the film formation chamber 50 is not particularly limited as long as the desired semiconductor film can be obtained, and is typically selected from an oxygen gas atmosphere, an inert gas atmosphere, a vacuum atmosphere, a reducing atmosphere, and an air atmosphere.

[0040] The semiconductor film thus obtained can be used as is or divided into semiconductor elements. Alternatively, the semiconductor film can be peeled off from the base substrate to form a single film. In this case, a release layer may be provided on the surface (film formation surface) of the base substrate in advance to facilitate peeling from the base substrate. Examples of such a release layer include a C-implanted layer or an H-implanted layer provided on the surface of the base substrate. Alternatively, C or H may be implanted into the semiconductor film during the initial film formation process, and the release layer may be provided on the semiconductor film side. Furthermore, a support substrate (mounting substrate) different from the base substrate can be bonded and attached to the surface of the semiconductor film formed on the base substrate (i.e., the surface opposite the base substrate), and then the base substrate can be peeled and removed from the semiconductor film. Such a support substrate (mounting substrate) can be one having a thermal expansion coefficient of 6 to 13 ppm / K at 25 to 400°C, such as a substrate made of a Cu-Mo composite metal. Examples of methods for bonding and joining the semiconductor film to the support substrate (mounting substrate) include known methods such as brazing, soldering, and solid-state bonding. Furthermore, an electrode such as an ohmic electrode or a Schottky electrode, or another layer such as an adhesive layer may be provided between the semiconductor film and the support substrate.

[0041] In the manufacture of semiconductor elements such as power devices, functional layers such as drift layers are formed on semiconductor films. Known methods can be used to form functional layers such as drift layers, and preferred examples include mist CVD, HVPE, MBE, MOCVD, and hydrothermal synthesis, with mist CVD or HVPE being particularly preferred.

[0042] Composite PCB The semiconductor film of the present invention can be manufactured by using a GaN single crystal substrate as a base substrate and depositing a film of an ε-GaO-based material thereon. That is, the present invention provides a composite substrate comprising a GaN single crystal substrate and the above-described semiconductor film formed on the GaN single crystal substrate. [Example]

[0043] The present invention is further illustrated by the following examples.

[0044] Example 1 (1) Preparation of ε-Ga2O3-based semiconductor films by mist CVD method (1a) Preparation of the base substrate As a base substrate, a c-plane GaN single crystal substrate having a thickness of approximately 0.4 mm and a diameter of 5.08 cm (2 inches) was prepared.

[0045] (1b) Preparation of raw material solution Metallic Ga was added to hydrochloric acid and stirred at room temperature for three weeks to obtain a gallium chloride solution with a gallium ion concentration of 3 mol / L. Water was added to the resulting gallium chloride solution to adjust the gallium ion concentration to 55 mmol / L. Ammonium hydroxide was added to this solution to adjust the pH to 4.0, creating the raw material solution.

[0046] (1c) Preparation for film formation A mist CVD apparatus 40 having the configuration shown in FIG. 3 was prepared. The configuration of the mist CVD apparatus 40 was as described above. In the mist CVD apparatus 40, the raw material solution L obtained in (1b) above was placed in the mist-generating chamber 42. A c-plane GaN substrate with a diameter of 5.08 cm (2 inches) was set on the stage 54 as the substrate 56, and the distance between the tip of the nozzle 52 and the substrate 56 was set to 120 mm. The temperature of the stage 54 was raised to 520°C using the heater 62 and maintained for 30 minutes to stabilize the temperature. The flow control valve (not shown) was opened to supply nitrogen gas as the carrier gas G into the film-forming chamber 50 via the mist-generating chamber 42, and the atmosphere in the film-forming chamber 50 was thoroughly replaced with the carrier gas G. The flow rate of the carrier gas G was then adjusted to 1.7 L / min.

[0047] (1d) Film formation The raw material solution L was atomized by the ultrasonic vibrator 46, and the generated mist M was introduced into the film formation chamber 50 by the carrier gas G. The mist M was reacted in the film formation chamber 50, particularly on the surface of the substrate 56 (specifically, a GaN substrate), to form a semiconductor film 58 on the substrate 56 over 60 minutes. The base substrate and film formation conditions are shown in Table 1.

[0048] (2) Evaluation of the semiconductor film (2a) Surface EDX As a result of performing EDX measurement on the obtained film surface, only Ga and O were detected, and it was found that the obtained film was a Ga oxide.

[0049] (2b) Surface EBSD Inverse pole figure orientation mapping of the Ga oxide film surface was carried out in a field of view of about 25 μm × 20 μm using a SEM (SU-5000, manufactured by Hitachi High-Tech Corporation) equipped with an electron backscatter diffraction device (EBSD) (Nordlys Nano, manufactured by Oxford Instruments). Using the software (Twist) attached to the device, crystal information such as the space group, unit cell parameters (sides and angles), and atomic positions of ε-Ga2O3 (hexagonal crystal) described in Non-Patent Document 4 (F. Mezzadri, et al., "Crystal Structure and Ferroelectric Properties of ε-Ga2O3Films Grown on (0001)-Sapphire," Inorg. Chem. 2016, 55, 12079-12084) was registered in the database, and EBSD measurement was performed using this.

[0050] The conditions for this EBSD measurement were as follows. <EBSD measurement conditions> ·Acceleration voltage: 15 kV ·Spot intensity: 70 ·Working distance: 22.5 mm ·Step size: 0.5 μm ·Sample tilt angle: 70° ·Measurement program: Aztec (version 3.3)

[0051] From the obtained inverse pole figure orientation mapping, it was found that the Ga oxide film had a biaxially oriented crystal structure with c-axis orientation in the substrate normal direction and in-plane orientation. From these results, it was confirmed that the obtained semiconductor film was an oriented film having a crystal structure composed of ε-Ga2O3.

[0052] (2c) Raman spectrum The Raman spectrum at the center point X of the film surface of the semiconductor film 58 and at the peripheral points A, B, C, and D was measured using a laser Raman spectrometer LabRAM ARAMIS manufactured by Horiba Ltd., and the operating software LabSpec (Ver. 5.78). The optical system was a Czerny-Turner type spectrometer, backscattering method, and a semiconductor pumped solid-state laser (DPSS, 532 nm) was used as the light source. Before measuring the sample, calibration was performed using a Si wafer. The Raman spectrum of the semiconductor film 58 was measured with the laser output adjusted to 24 mW, the hole (confocal hole diameter) set to 400 μm, and the central wave number of the spectrometer set to 520 cm. -1 The slit was 100 μm, the grating was 1800 gr / mm, the objective lens was 100x, and the analysis was performed in point analysis mode. The exposure time was 60 seconds, the number of integrations was 2, and the wavenumber range was 100-900 cm. -1 The neutral density filter was appropriately set so that the count of the strongest peak was between 3,000 and 50,000. In addition, a Ne lamp was used during measurement, and the wave number of the peak top due to the Ne lamp emission line in the obtained spectrum was 278.28 cm. -1 The spectrum was corrected so that the baseline was corrected. Baseline correction was performed using the software LabSpec, with "Type" set to "Lines," "Degree" set to "5," "Attach" set to "No," "Style" set to "-," and "Auto." The spectrum obtained in this way is shown in Figure 4. The spectrum obtained was analyzed by measuring the 250 cm at the center point X and the outer periphery points A, B, C, and D. -1 The wavenumber of the peak top of the peak in the vicinity is N X , N A , N B , N C and N D , and 113cm -1 The wavenumber of the peak top of the peak in the vicinity is N X , N A , N B , N C and N D In addition, the wave number N X , N A , N B, N C and N D The full width at half maximum in is W X , W A , W B , W C and W D were designated as such. Further, the peak intensity I -1 at the peak with a peak top near 250 cm at the center point X and the outer peripheral points A, B, C, and D 250 The peak intensity ratio I -1 at 260 cm of I 260 with respect to the peak intensity I 250 / I 260 was determined. In this example, for instance, the wavenumber N -1 of the peak top of the peak near 250 cm X was 251.1 cm -1 and when the full width at half maximum W X for this peak was calculated, it was 8.8 cm -1 and it was found that it was highly crystalline ε-Ga2O3. The results were as shown in Table 2.

[0053] (2d) Concentration of each element Using a secondary ion mass spectrometer (SIMS), the composition analysis of the film surface of ε-Ga2O3 was performed and the concentrations of Fe, Ti, Na, F, and Si were measured. The conditions for this D-SIMS analysis were as follows. The results were as shown in Table 2.

[0054] <D-SIMS analysis conditions (when detecting Fe, Ti, and Na)> · Elements of interest: Fe, Ti, Na · Apparatus: IMS-7f manufactured by CAMECA · Primary ion species: O2 2+ · Primary ion acceleration energy: 8 keV · Secondary ion polarity: Positive · Detection area: 30 μm in diameter

[0055] <D-SIMS analysis conditions (when detecting F and Si)> · Elements of interest: F, Si Equipment: CAMECA IMS-7f Primary ion species: Cs + Primary ion acceleration energy: 15.0 keV Secondary ion polarity: Negative Detection area: 30μm diameter

[0056] Example 2 In the above (1c) and (1d), when forming a film by mist CVD, the temperature of the stage 54 was stabilized at 500°C before starting film formation, and the temperature was raised to 520°C over 20 minutes. Except for this, the semiconductor film was prepared and various evaluations were carried out in the same manner as in Example 1. -1 Wave number N of the peak top of the nearby peak X 246.8cm -1 and the half-width for this peak W X The calculated result was 6.7cm -1 From this, 250cm -1 The peaks around 1000 nm were found to be sharp. The semiconductor film also had a low impurity concentration. The results are shown in Tables 1 and 2.

[0057] Example 3 Various evaluations were carried out in the same manner as in Example 1, except that the ε-Ga2O3-based semiconductor film was fabricated by the HVPE method described below instead of the mist CVD method (above (1)). -1 Wave number N of the peak top of the nearby peak X 248.3cm -1 and the half-width for this peak W X The calculated result was 7.0 cm -1 From this, 250cm -1 The peaks around 1000 nm were found to be sharp. The semiconductor film also had a low impurity concentration. The results are shown in Tables 1 and 2.

[0058] (1') Preparation of ε-Ga2O3-based semiconductor films by HVPE (1a') Preparation of the base substrate As a base substrate, a c-plane GaN single crystal substrate having a thickness of approximately 0.4 mm and a diameter of 5.08 cm (2 inches) was prepared.

[0059] (1b') Film formation An HVPE apparatus 20 having the configuration shown in Figure 2 was prepared. The configuration of the HVPE apparatus 20 was as described above. Metallic Ga was placed in a reactor 22, and hydrogen chloride gas (HCl) was supplied. This caused the metallic Ga and hydrogen chloride to react with each other, generating Ga halide, which was then supplied to a base substrate 24 for film formation. At the same time, O2 gas as an oxygen source and N2 gas as a carrier gas were introduced into the reactor 22. In this way, film formation by the HVPE method was carried out at a growth temperature of 550°C for 15 minutes, yielding a base substrate 24 for film formation and a semiconductor film formed thereon as a composite material.

[0060] Example 4 In the above (1b') in the HVPE method, the growth temperature was stabilized at 550°C before film formation was started, and the temperature was then raised to 580°C over 30 minutes, but the same procedures as in Example 3 were carried out to prepare the semiconductor film and perform various evaluations. -1 Wave number N of the peak top of the nearby peak X 254.9cm -1 and the half-width for this peak W X The calculated result was 5.9 cm -1 From this, 250cm -1 The peaks around 1000 nm were found to be sharp. The semiconductor film also had a low impurity concentration. The results are shown in Tables 1 and 2.

[0061] Example 5 (comparison) In the mist CVD method (1c) and (1d) described above, the temperature of the stage 54 was stabilized at 500°C during film formation, and the semiconductor film was fabricated and various evaluations were carried out in the same manner as in Example 1. -1 Wave number N of the peak top of the nearby peak X 251.9cm -1and the half-width for this peak W X The calculation was 16.5cm -1 From this, 250cm -1 The peak around 1000 nm was found to be broad. The semiconductor film had a high impurity concentration. The results are shown in Tables 1 and 2.

[0062] Example 6 (comparison) In the above (1b') in the HVPE method, the semiconductor film was prepared and various evaluations were carried out in the same manner as in Example 3, except that the growth temperature was stabilized at 500°C. -1 Wave number N of the peak top of the nearby peak X 251.7cm -1 and the half-width for this peak W X The calculated result was 14.3 cm -1 From this, 250cm -1 The peak around 1000 nm was found to be broad. The semiconductor film had a high impurity concentration. The results are shown in Tables 1 and 2.

[0063] [Table 1]

[0064] [Table 2]

Claims

1. ε-Ga 2 O 3 , or ε-Ga 2 O 3 A semiconductor film having a crystal phase mainly composed of a solid solution of the system, The semiconductor film has a peak at 250 cm in the Raman spectrum measured by laser Raman spectroscopy. -1 The half-width of the peak in the vicinity is 10 cm -1 is as follows: the half-width of a peak near 250 cm −1 in a Raman spectrum of the semiconductor film measured by laser Raman spectroscopy at a center point X of the largest circle inscribed in the outer periphery of the semiconductor film and at each of four outer periphery points A, B, C and D on the surface of the semiconductor film is 10 cm −1 or less; the outer periphery points A, B, C, and D are determined such that i) a straight line connecting the outer periphery points A and C and a straight line connecting the outer periphery points B and D intersect at a right angle at the center point X, and ii) the shortest distance from the outer edge of the semiconductor film to each of the outer periphery points A, B, C, and D is 1 / 5 of the radius of the semiconductor film; The semiconductor film has a size such that the diameter of the maximum circle inscribed on the outer periphery of the semiconductor film is 5.08 cm or more.

2. In the Raman spectrum of the semiconductor film, -1 Peak intensity I near 250 260cm -1 Peak intensity I near 260 Peak intensity ratio I 250 / I 260 The semiconductor film according to claim 1 , wherein is 2.0 or more.

3. The semiconductor film had a Raman spectrum of 113 cm -1 The half-width of the peak in the vicinity is 10 cm -1 3. The semiconductor film according to claim 1, wherein:

4. The Ti concentration at the surface of the semiconductor film is 1.0×10 15 atoms / cm 3 3. The semiconductor film according to claim 1, wherein:

5. The Fe concentration at the surface of the semiconductor film is 1.0×10 15 atoms / cm 3 3. The semiconductor film according to claim 1, wherein:

6. The Na concentration at the surface of the semiconductor film is 2.0×10 13 atoms / cm 3 3. The semiconductor film according to claim 1, wherein:

7. The F concentration at the surface of the semiconductor film is 2.0×10 15 atoms / cm 3 3. The semiconductor film according to claim 1, wherein:

8. The Si concentration at the surface of the semiconductor film is 1.0×10 16 atoms / cm 3 3. The semiconductor film according to claim 1, wherein:

9. A composite substrate comprising a GaN single crystal substrate and the semiconductor film according to claim 1 or 2 formed on the GaN single crystal substrate.

Citation Information

Patent Citations

  • Method for regulating and controlling photoelectric response performance of epsilon-phase gallium oxide through oxygen vacancy concentration

    CN113066902A

  • Motor-operated remote-controlled mirror device

    JP1989036538A

  • ε-Ga2O3 SINGLE CRYSTAL, PRODUCTION METHOD FOR ε-Ga2O3, AND SEMICONDUCTOR ELEMENT USING THE SAME

    JP2017007871A

  • Laminate structure and semiconductor device

    JP2019009405A

  • Gallium nitride semiconductor substrate, gallium nitride semiconductor device, imaging device, and manufacturing method thereof

    JP2019012826A